Manajemen risiko kepatuhan di lembaga keuangan syariah : tinjauan konseptual dan regulasi - vio m, anggun milania (Maliki Interdisciplinary Journal, 2025)
Compliance risk is a critical issue in ensuring the integrity and sustainability of Islamic financial institutions. This risk arises when institutions fail to comply with applicable regulations or violate the principles of Sharia. This study aims to explore the conceptual foundation of compliance risk management, examine the regulatory framework governing Islamic financial institutions, analyze the alignment with Sharia governance principles, and identify major challenges and strategic solutions. Using a literature review method, this research synthesizes findings from academic journals, regulatory documents, and previous studies relevant to compliance practices in Islamic banking. The results show that effective compliance risk management requires a robust Sharia governance structure, competent and independent Sharia Supervisory Boards, and strong internal coordination. The challenges include limited Sharia literacy among personnel, inadequate technical regulations, and weak organizational integration. To address these issues, Islamic banks must invest in continuous training, establish independent Sharia compliance units, and enhance transparency in handling non-halal funds. Strengthening compliance culture and regulatory harmonization—both nationally and regionally—are key to building trustworthy and resilient Islamic financial institutions in the face of global economic dynamics.